Venus: Scalable Real-time Spatial Queries on Microblogs with Adaptive Load Shedding - Magdy, Amr; Mokbel, Mohamed F.; Elnikety, Sameh; Nath, Suman; He, Yuxiong (IEEE Transactions on Knowledge and Data Engineering, 2016)
Microblogging services have become among the most popular services on the web in the last few years.